Roxadustat for renal anemia: current clinical experience - Ji, Jialing; Li, Zhongtang; Fang, Shuping; Li, Zuolin (Frontiers in Pharmacology, 2026)
Anemia represents one of the most prevalent complications of chronic kidney disease (CKD). Investigation of the regulation of erythropoietin production led to the discovery of oxygen-sensing mechanisms, which are now being targeted therapeutically (hypoxia-inducible factor prolyl hydroxylase inhibitors, HIF-PHI). Roxadustat, a first-in-class of HIF-PHI, achieved its first approval in China in December 2018 for managing anemia in adult patients with CKD. Over the past 6 years, we have gained substantial real-world experience regarding its therapeutic application. Accordingly, accumulated evidence demonstrates that roxadustat is superior to placebo and non-inferior to current standard-of-care erythropoiesis-stimulating agents in correcting and maintaining hemoglobin concentration at target levels among patients with non-dialysis dependent CKD and incident and dialysis dependent CKD. However, given the pleiotropic effects of HIF activation, the pharmacologic activation of HIF in patients with anemia of CKD is also likely to have effects beyond erythropoiesis and iron metabolism. In this review, we synthesize clinical insights from these novel therapeutics and highlight some of the outstanding questions relevant to their clinical use. This study may provide theoretical framework and practical evidence for the clinical application of other HIF-PHIs.